Petrochemistry and mineralogy of pumice from the Sarychev Peak Volcano, Matua Island, Central Kuril Island - V. M. Okrugin; E. D. Skilskaia; S. V. Moskaleva (Известия высших учебных заведений: Геология и разведка, 2022)
Background. The article presents the first results of a mineralogical and petrographic study of the pumice of the Sarychev Peak volcano, Matua island, the Central Kuril islands.Aim. To reconstruct the compositions of magmatic melts of a caldera-forming eruption of the proto-Matua volcano.Materials and methods. The main research methods included an X-ray fluorescence spectral analysis to determine the content of petrogenic, rare and trace elements, as well as an electron-probe microanalysis to study variations in the chemical composition of mineral inclusions of pumice.Results and conclusion. According to the content of SiO2 and the sum of alkalis, the composition of pumice varies from andesibasaltes (SiO2 = 55.94 wt.%) to dacites (SiO2 = 67.70 wt.%). According to the content of K2O, pumice can be classified as a moderate-potassium series of rocks. The inclusion minerals represented by plagioclase, amphibole, apatite and Fe-Ti oxides were crystallized at the same time from a water-saturated magmatic melt at a pressure of about 1.5–2.2 kbar. The igneous melt was enriched with volatile components of H2O, CO2, S, F and Cl.